Analysis of Supply Chain Beef Cattle in Riau Province - Zamaya, Yelly; Pramana, Angga; Ningsih, Arum Rovarti; Kurnia, Dihan (Jurnal Ilmu dan Teknologi Peternakan Tropis, 2022)
The livestock sector plays a strategic role in the economy of Riau Province through the contribution of food supply, supply of industrial raw materials, feed, bio-energy, employment, and achievement of GRDP (Gross Regional Domestic Product). One of the commodities in the livestock sector that has the potential to be developed is beef. This study aims to analyze the supply chain flow and determine the beef supply chain strategy in Riau Province. The research method used is descriptive qualitative analysis. Qualitative descriptive analysis using SWOT analysis on the beef supply chain. There are 4 streams of the beef supply chain in Riau Province. First, producers/breeders and consumers; second, breeders, traders, and consumers; third, breeders, traders, slaughterhouses, and consumers; fourth, namely breeders, blantik, butchers, wholesalers, and small traders then bought by consumers. The internal factor evaluation matrix has a total score of 2.6807, while the external factor evaluation matrix has a total score of 2.7432. The strength factor of the beef supply chain is the quality of beef cattle is good, the weakness factor is the continuity of beef cattle supply is still lacking, the opportunity factor is the wide open market share, and the threat factor is he instability of beef supply.